The impact of glidant addition on the loss-in-weight feeding of active pharmaceutical ingredients - Verbeek, Tom; De Man, Alexander; Debacker, Melissa; Bekaert, Bram; Van Snick, Bernd; Otava, Martin; Vervaet, Chris; Vanhoorne, Valérie (International journal of pharmaceutics, 2025)
In recent years, CM has become increasingly popular in the pharmaceutical industry for the production of OSD forms. Most of the newly developed APIs nowadays are extremely cohesive and sticky with a mean particle size particle of <100 μm, a wide PSD and a high tendency to agglomerate, making them difficult to accurately dose using loss-in-weight equipment during CM. In this research paper, the effect of various glidants on the volumetric and gravimetric feeding of several APIs was assessed. Three challenging API (APAPμ, MPT and SD) and four different glidants (Aerosil® 200, Aerosil® R972, Syloid® 244FP and TRI-CAFOS® 200-7) were selected. For all feeding trials, a GEA CF equipped with 20 mm concave screws was used, in combination with an external catch scale. The volumetric feeding trials showed the ability of each glidant to increase the FFmax and reduce the FFmovRSD40 and the FFdecay for the cohesive APIs (APAPμ and MPT). Although the fumed silica grades showed the highest impact on the previously mentioned feeding parameters, low AE10 values were obtained, negatively affecting the feeding performance at higher glidant concentration. Both Syloid 244FP and TCP were good alternatives. However, to obtain a similar feeding performance a higher concentration of these glidants is required. The volumetric trials showed that glidant addition has no additional benefits for APIs with good flow properties such as SD. The second part of this paper discussed the impact of glidant addition on the gravimetric feeding behavior of the cohesive powders. Both the fumed silica grades (Aerosil® 200 and Aerosil® R972) and Syloid 244FP lowered the deviation on all LC% profiles of the cohesive APIs. In contrast to the volumetric trails, blends with excess fumed silica resulted in low AE10 values which are efficiently dosed by the CF during the gravimetric feeding.
Keywords: Continuous manufacturing; oxid křemičitý; prášky, zásypy, pudry; Loss-in-weight feeding; Excipients; Powders; farmaceutická chemie; Bulk Drugs; pomocné látky; Particle engineering; Drug Compounding; Chemistry, Pharmaceutical; nerozplněné léky; velikost částic; Flow enhancers; léčivé přípravky; Continuous direct compression; Silicon Dioxide; příprava léků; Pharmaceutical Preparations; Particle Size; Glidants; Formulation development